Separation of Sulfate Anion From Aqueous Solution Governed by Recognition Chemistry: A Minireview - Chen, Si-Qi; Zhao, Wei; Wu, Biao (Frontiers in Chemistry, 2022)
Sulfate anion (SO42–) is known as an end metabolite of cysteine and methionine, and its proper concentration associates with expression of key functions in physiological system. Thus, maintaining sulfate concentration in precise level is of great significance for biology, environments, and industrial productions. Fundamental research for sulfate anion chemistry can help to understand sulfate-associated physiological processes and related applications, e.g., remediation. In this minireview, we summarized recent research progresses in sulfate recognition and separation using crystallization and liquid-liquid extraction. We focused on the studies that molecular recognition is the key element and considered as the driving force for selective sulfate separations from aqueous solution.